Whistle While You Work: Toward a Model of Emotional Self-Leadership. (November 2016) - Manz, Charles C.; Houghton, Jeffery D.; Neck, Christopher P.; Fugate, Mel; Pearce, Craig
There has been a growing interest in leader emotion in organizational scholarship. Concomitantly, the body of research on self-leadership continues to expand. Nonetheless, relatively little work has focused on emotional self-leadership . We address this void by exploring intrapersonal and interpersonal aspects of emotional self-leadership and its inherent challenges and opportunities. Specifically, we examine how emotional self-leadership strategies can be used to shape emotional experiences, emotional authenticity, and other work-related outcomes. We offer an emotional self-leadership model, research propositions, and implications for research and practice.